Part-time or Full-time Employment: Choices and Constraints - Ingstad, Kari; Hedlund, Marianne (Nordic Journal of Working Life Studies, 2017)
This article explores nurses’ working-hour practices in Norwegian nursing homes through a career path. Although the nursing profession is dominated by women and is a typical part-time occupation, this study found variations in working-hour patterns among nurses. These variations suggest that nurses not only have different career patterns but also that the working hours of individual nurses vary throughout a career. The analysis highlights different contextual factors that influence nurses’ working hours during their careers. The findings are based on data collected through in-depth interviews with 22 nurses over the age of 56. As a result, we conclude that the working-hour patterns of nurses are constructed out of interactions among the welfare state, the labor market, and family practices, meaning that workinghour patterns can be influenced and changed.